Kebijakan Stock Split Perusahaan Non-Financial Di Indonesia: Manajemen Laba, Kinerja Operasi, Kinerja Pasar - Amrie Firmansyah; Titi Sari Indriani (Politeknik Ganesha Medan, 2021)
The stock split policy shows the success of managers in managing the company. The condition of managers who have perfect information compared to shareholders, stock split policies may coincide with certain motives carried out by managers. This study examines differences in earnings management, operating performance, and market performance before and after the company conducts a stock split. This study employs secondary data sourced from www.idx.co.id, www.idnfinansials.com, and www.finance.yahoo.com. The data employed consists of data and information from financial statements and stock prices of non-financial companies listed on the Indonesia Stock Exchange from 2013 to 2019. The sample used in this study amounted to 64 observations based on purposive sampling. The data analysis test used the normality test and the Wilcoxon matched-pairs test. This study concludes that earnings management and market performance increase after the company's stock split is carried out. Meanwhile, operating performance did not experience any difference before and after the stock split was carried out. This study proves that managers employ the moment stock split to carry out earnings management for certain motives, even though the market participants positively respond to these actions. The companies that carry out stock splits should make these events to improve their operating performance. This study indicates that the Financial Services Authority needs to review companies with plans to conduct a stock split to protect investors in the capital market